Interrelations between factors in the development of inflammatory changes in the urinary tract in the comprehensive treatment of patients with urolithiasis - O. O. Lyulko; V. O. Morhuntsov (Zaporožskij Medicinskij Žurnal)
The aim of the work is to analyze the scientific literature data on the principles and state of rational antibiotic therapy use according to factors for the development of inflammatory changes in the urinary tract with the identification of the latter in the complex therapy for urolithiasis, taking into account the peculiarities of contact laser lithotripsy.